Preserving mental well-being amidst a litigious society: the way forward for Muslim medical professionals - Jahn Kassim, Puteri Nemie (2021)
The growing number of litigated medical negligence cases in Malaysia has put a tremendous pressure on the medical profession. As patient autonomy is given more credence in the Malaysian judicial decisions, patients are seen to be more and more victorious in procuring high amount of monetary compensation in the litigated cases. This phenomenon has caused the medical profession to fear for the loss of livelihood, their damaged reputation while magnifying feelings of negativity, anger, self-reproach, anxiety, depression, and isolation. The threat of future litigation has also caused the practice of defensive medicine amongst the medical professionals and slowly destroying their cordial relationship with their patients by inculcating confrontational elements between them. Hence, in preserving their mental health and well-being amidst the hazards of court litigation, Muslim medical professionals need to get a proper insight and understanding of the Islamic Medical Ethics which foundation is based upon the primary sources of the Shari’ah namely, the Holy Quran and the Sunnah of the Prophet Muhammad pbuh. Understanding and applying the salient principles inherent in the Islamic ethical theory will enable the Muslim medical professionals to provide a much more sensitive and satisfying healthcare delivery towards their patients and ultimately, defuse the spur of litigation amongst members of the society.